Acceptance and use of mobile banking: an application of UTAUT2. Issue 1 (29th August 2018) - Owusu Kwateng, Kwame; Osei Atiemo, Kenneth Afo; Appiah, Charity
Abstract : Purpose: Mobile banking (m-banking) can be defined as a service offered by a bank or any other financial institution that allows the customers of such establishments to carry out a variety of banking operations via a mobile device, such as a mobile phone, tablet or personal digital assistant. The purpose of this paper is to examine factors that influence customers to adopt and subsequently use m-banking services in Ghana using the unified theory of acceptance and use of technology 2 (UTAUT2) model with age, educational level, user experience and gender as moderators. Design/methodology/approach: Using questionnaire survey, the study sampled 300 users of m-banking services in Ghana as respondents. The primary data collected were analyzed using SmartPLS software. Findings: Findings of the study indicate that Habit, Price Value and Trust are the main factors influencing adoption and use of m-banking in Ghana. Individual differences of gender, age, educational level and user experience responded differently as they moderate the relationship between UTAUT2 constructs and use bahaviour. The applicability of UTAUT2 model was confirmed in the context of the research. Practical implications: M-banking is a new phenomenon in Ghana's financial industry, thus it is imperative to understanding the customer adoption behavior. The outcome will aid financial institutions to develop strategies that will sustain the interest of consumers to embrace m-banking. Originality/value: This paper is among the first ever known attempts to examine m-banking adoption in Ghana using UTAUT2 model.